Biodegradable and bioactive polymer/inorganic phase nanocomposites for bone tissue engineering (BTE) - Miguez-Pacheco, Valentina; Misra, S. K.; Boccaccini, Aldo R. (Elsevier Inc., 2014)
Scaffolds for bone tissue engineering (BTE) must be mechanically competent and chemically compatible with bone tissue to repair defects. Polymeric materials exhibit suitable mechanical and processing abilities but lack the bioactivity of inorganic ceramics. Composites of these materials are being developed to combine and improve their properties. It has become evident that cells respond to the topography of the surrounding extracellular matrix, specifically to nano-sized features; and reproducing these physical characteristics on the surface of scaffolds improves cell spread and attachment. Electrospinning can produce thin fibres with wide-ranging diameters and offers the possibility of fabricating nanocomposite fibrous scaffolds. This chapter focuses on ascertaining the impact of an inorganic phase on the mechanical properties, bioactivity and cell behaviour of electrospun composite structures.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Bioactivity; Bone scaffolds; Electrospinning; Nanocomposites